Anti-inflammatory and antioxidant properties of chemical constituents of Broussonetia papyrifera - Malaník, Milan; Treml, Jakub; Leláková, Veronika; Nykodýmová, Daniela; Oravec, Michal; Marek, Jaromír; Šmejkal, Karel (Bioorganic chemistry, 2020)
Extensive phytochemical analysis of the CHCl3-soluble part of an ethanolic extract of branches and twigs of Broussonetia papyrifera led to the isolation of fourteen compounds, including a novel 5,11-dioxabenzo[b]fluoren-10-one derivative named broussofluorenone C (12). The isolated compounds 1-14 were characterized based on their NMR and HRMS data, and examined for their anti-inflammatory activities in LPS-stimulated THP-1 cells as well as for their cellular antioxidant effects. Compounds 7-10 and 12 showed inhibitory effects on NF-κB/AP-1 activation and compounds 7-9 were subsequently confirmed to suppress the secretion of both IL-1β and TNF-α in LPS-stimulated THP-1 cells more significantly than the prednisone used as a positive control. In the CAA assay, compound 10 exhibited the greatest antioxidant effect, greater than that of the quercetin used as a positive control. The results show possible beneficial effects and utilization of B. papyrifera wood in the treatment of inflammatory diseases as well as oxidative stress.
Keywords: antiflogistika; Broussonetia papyrifera; vztah mezi dávkou a účinkem léčiva; Antioxidants; THP-1 buňky; lipopolysacharidy; Transcription Factor AP-1; oxidační stres; Antioxidant; Tumor Necrosis Factor-alpha; Broussonetia; Oxidative Stress; Molecular Structure; Structure-Activity Relationship; lidé; THP-1 Cells; NF-κB; Lipopolysaccharides; kultivované buňky; molekulární struktura; Cells, Cultured; transkripční faktor AP-1; TNF-alfa; Dose-Response Relationship, Drug; Interleukin-1beta; Anti-Inflammatory Agents; antioxidancia; vztahy mezi strukturou a aktivitou; interleukin-1beta; Anti-inflammatory; Cell Survival; NF-kappa B; viabilita buněk; Humans